PENGARUH PROSES PRODUKSI TERHADAP PEMASARAN KERUPUK DI DESA BABADAN KECAMATAN PANGKUR KABUPATEN NGAWI TAHUN 2009/2011 - Pujianto Pujianto (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
Agus cracker  factory  in the village  of Babadan  show  lack  of broader  marketing. This  is due to the lack of optimal  production   processes  and equipment   labour making process  that affect  the marketing   of crackers.   So that there was  influence  of the Produc- tion Process  Of Marketing   cracker   in the Village  District  Babadan    pickaxe  Ngawi  Re- gency Year 2009/2011. This  study  aims  to determine   the effect  of the production   process to marketing   cracker  in the Village District   Babadan  pickaxe  Ngawi  Regency  Year 2009/2011.  In this  researh   using  survey   methods   this  can  be  seen  through   title  research   to determine   the effect  between   variables.  The  sample   in this  study  using  the  technique   of saturated   samples   sampling   technique   when  all members   of the  population   are  used  as samples.   Collecting   data  using  secondary   data.  In analyzing   the data using  a simple  re- gression   analysis   and  t-test.  The  results   of  analyses   of data  all  the production    process (X I) to marketing   (Y) shows  tcount for 2635> ttable of 2.032.    He means  acceptable   means there  is the influence  of the production   process  to marketing.   If the production   increased by 1 % as well as the marketing   will increase  0.597%,   while  the other factors  being  equal. In addition   to the value  obtained   for  the regression   equation   are  value  for R2. From  the test results  on the effects  of the production    process  F (X I)  to marketing   (Y)  shows  the test results  above  it can be seen  that the value  of  Fcount   6.943 >=  Ftable.    Of 3.286    at a signifi- cance  level  of 0.05.  This  means  that the Ha  accepted,   meaning   that  the production   pro- cess  affects  the marketing   of crackers  in the village  district  Babadan  pickaxe  years 2009-2011.  Moreover.   it can be said  that there  is a linear  relationship   between  the production   to marketing.   From  the results  of this study  concluded   that tbere  was  an effect  of the  pro- duction   process   to  the  marketing   of crackers   in  the  Village   District   Babadan   pickaxe Ngawi  Regency   Year  2009/2011.   This   is demonstrated    by  the  acquisition    of  the  data analysis.